Scientific-Practical Conference "Integrity of Subject Knowledge and Pedagogical Practice". Conference Program and Abstract Book - Grigorjevaitė, Julija; Kizalaitė, Agnė (Vilnius University Proceedings, 2026)
On March 20–21, 2026, the scientific-practical conference "Integrity of Subject Knowledge and Pedagogical Practice" took place. This event marked the conclusion of the national professional development program, "Improvement of Subject-Specific and Didactic Competencies for Chemistry Teachers" which had been ongoing since October 1, 2025. The national professional development program is designed for chemistry teachers working with students in grades 8–12. The program aims to strengthen teachers’ subject-specific and didactic competencies, focusing on the updated primary and secondary chemistry curricula, which emphasize inquiry-based learning. This event serves as a platform for the chemistry teaching community to gather, share accumulated experience, and discuss the practical application of the latest didactic insights in daily classroom settings.